A thermally populated, perpendicularly twisted alkene triplet diradical - Wentrup, Curt; Müller, Dennis; Comba, Peter (Angewandte Chemie. International edition, 2016)
Variable-temperature NMR and ESR spectroscopic studies reveal that bis(dibenzo[a,i]fluorenylidene) possesses a singlet ground state, 1(S0), while the 90° twisted triplet(T1) is populated to a small extent already at room temperature. Analysis of the increasing amount of paramagnetic(T1) at temperatures between 300 and 500 K yields the exchange interaction Jex/h c=3351 cm−1 and a singlet-triplet energy splitting of 9.6 kcal mol−1, which is in excellent agreement with calculations (9.3 kcal mol−1 at the UKS BP86/B3LYP/revPBE level of theory). In contrast, the zero-field splitting parameter D is very small (calculated value −0.018 cm−1) and unmeasurable.